Laser interstitial thermal therapy is effective and safe for the treatment of brain tumors in NF1 patients after cerebral revascularization for moyamoya angiopathy: a report on two cases - Guida, Lelio; Beccaria, Kevin; Benichi, Sandro; Kossorotof, Manoelle; Naggara, Olivier; Bourgeois, Marie; Bourdeaut, Franck; Abbou, Samuel; Dangouloff-Ros, Volodia; Boddaert, Nathalie; Blauwblomme, Thomas (Frontiers in Neurology, 2023)
Background The co-occurrence of moyamoya vasculopathy and extra-optic pathway tumors is rare in neurofibromatosis type 1 (NF1), with only four cases described in the literature. Brain surgery in these patients may be challenging because of the risk of brain infarction after skin and dural incision. Given its percutaneous and minimally invasive nature, laser interstitial thermal therapy (LITT) is an ideal option for the treatment of brain tumors in these patients. Here, we report on two patients with NF1 and moyamoya syndrome (MMS) treated for a brain glioma with LITT, after cerebral revascularization. Cases The first patient, with familial NF1, underwent bilateral indirect revascularization with multiple burr holes (MBH) for symptomatic MMS. Two years later, she was diagnosed with a left temporal tumor, with evidence of radiologic progression over 10 months. The second patient, also with familial NF1, developed unilateral MMS when he was 6 years old and was treated with MBH. At the age of 15 years, MRI showed a right cingular lesion, growing on serial MRIs. Both patients underwent LITT with no perioperative complications; they are progression free at 10 and 12 months, respectively, and the tumors have decreased in volume. Discussion While the association of extra-optic neoplasm and moyamoya angiopathy is seldom reported in NF1, tumor treatment is challenging in terms of both avoiding stroke and achieving oncological control. Here, we show in 2 cases, that LITT could be a safe and effective option in these rare conditions.